Neurotensin-loaded collagen dressings reduce inflammation and improve wound healing in diabetic mice - Moura, Liane I. F. (2014)
Impaired wound healing is an important clinical problem in diabetes mellitus and results in failure to completely heal diabetic foot ulcers (DFUs), which may lead to lower extremity amputations. In the present study, collagen based dressings were prepared to be applied as support for the delivery of neurotensin (NT), a neuropeptide that acts as an inflammatory modulator in wound healing. The performance of NT alone and NT–loaded collagen matrices to treat wounds in streptozotocin (STZ) diabetic induced mice was evaluated. Results showed that the prepared dressings were not-cytotoxic up to 72 h after contact with macrophages (Raw 264.7) and human keratinocyte (HaCaT) cell lines. Moreover, those cells were shown to adhere to the collagen matrices without noticeable change in their morphology. NT–loaded collagen dressings induced faster healing (17% wound area reduction) in the early phases of wound healing in diabetic wounded mice. In addition, they also significantly reduced inflammatory cytokine expression namely, TNF-α (p < 0.01) and IL-1β (p < 0.01) and decreased the inflammatory infiltrate at day 3 post-wounding (inflammatory phase). After complete healing, metalloproteinase 9 (MMP-9) is reduced in diabetic skin (p < 0.05) which significantly increased fibroblast migration and collagen (collagen type I, alpha 2 (COL1A2) and collagen type III, alpha 1 (COL3A1)) expression and deposition. These results suggest that collagen-based dressings can be an effective support for NT release into diabetic wound enhancing the healing process. Nevertheless, a more prominent scar is observed in diabetic wounds treated with collagen when compared to the treatment with NT alone.